Effective internal audit: A performance index / Razimah Abdullah - Abdullah, Razimah (2009)
Audits have been present since the Egyptian and Roman Empires in relation to the principal-agency relationship. Corporate governance is the way in which those managing an organisation (the agents) carry out their responsibilities towards their stakeholders (the principal). Agency problems mainly due to wealth maximization of agents result in agency costs detrimental to the principal. Internal audit acts as a monitoring mechanism within the organisation. Poor corporate governance has pointed to the ineffectiveness of internal audits to report on possible mismanagement, thus failing to give indications for preventive measures to be taken in due course by the management and stakeholders. World disasters like Enron, WorldCom and HIH group are classical cases in recent times. This calls for a measurement on the effectiveness of internal audits. The purpose of this research is to measure the effectiveness of internal audits conducted by internal auditors. The data were collected by way of questionnaire survey sent to internal auditors in Malaysian public institutions of higher learning and corporate members of the Institute of Internal Auditors Malaysia. The study considers the internal audit activities from the planning stage to the follow-up of reported audit findings. Best practices in internal auditing have been reviewed taking into account activities within the audit process cycle. Results suggest that the effectiveness of the internal audit can be measured by using a performance index and the indicators used provide reasonable insight into the internal audit activities assessed. The significant of deriving at an internal audit index may serve as a benchmark of best practices in internal audit. The internal audit activities assessed in this study give some indication of areas for improvement to be considered in the management of the internal audit function. It is the novelty of this unidimensional measurement method where it can be further applied to all other institutions of higher learning to determine the effectiveness of their internal audit, hence useful for national benchmarking purposes.